2003
DOI: 10.1093/treephys/23.10.705
|View full text |Cite
|
Sign up to set email alerts
|

Growth, photosynthetic performance and shade adaptation of rubber (Hevea brasiliensis) grown in natural shade

Abstract: We compared growth, photosynthetic performance and shade adaptation of rubber (Hevea brasiliensis Muell. Arg.) plants growing in natural shade (33, 55 and 77% reduction in incoming radiation) to control plants growing in full sunlight. Stem diameter and plant height, measured over a 15-month period, were greatest in plants grown in full sunlight, and both parameters decreased with increasing shade. At 7 and 14 months after planting (MAP), total plant dry mass was highest in control plants and lowest in plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
10
29
0
5
Order By: Relevance
“…In stage D (57 th day), when the leaves were fully expanded and mature, clones PB 235, RRIM 600 and GT 1 showed values of Fv / Fm ratio correspondent to 0.75, 0.79 and 0.77, respectively. Those values were similar to the results found by Senevirathna et al (2003) in fully expanded leaves of rubber tree cultivated under field conditions. The lowest values of Fv / Fm ratio presented by clone GT 1, possibly are due to a greater increase of Fo relative to Fm, which implicates reduction of Fv.…”
Section: Resultssupporting
confidence: 91%
“…In stage D (57 th day), when the leaves were fully expanded and mature, clones PB 235, RRIM 600 and GT 1 showed values of Fv / Fm ratio correspondent to 0.75, 0.79 and 0.77, respectively. Those values were similar to the results found by Senevirathna et al (2003) in fully expanded leaves of rubber tree cultivated under field conditions. The lowest values of Fv / Fm ratio presented by clone GT 1, possibly are due to a greater increase of Fo relative to Fm, which implicates reduction of Fv.…”
Section: Resultssupporting
confidence: 91%
“…The Aluminet ® environment led to the clones larger number of leaves than the environment in full sun (Table 2), which is consistent with SENEVIRATHNA et al (2003) and CONFORTO et al (2011) in which Hevea brasiliensis plants showed higher number of leaves in shaded environments than in full sun. SENEVIRATHNA et al (2003) reported also that the CO2 absorption saturation occurs at a lower density photosynthetic radiation flux in shaded plants.…”
Section: Environmentssupporting
confidence: 80%
“…SENEVIRATHNA et al (2003) reported also that the CO2 absorption saturation occurs at a lower density photosynthetic radiation flux in shaded plants. In the environment with aluminized screen there was higher relative humidity and radiation sufficient to saturate the assimilation of CO2 without harming the photosynthetic efficiency (Figure 1), environmental conditions that propitiated the best seedlings.…”
Section: Environmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Folhas de sol geralmente são mais grossas (Lima Junior et al, 2005); têm maior superfície de mesofilo por unidade de área foliar (Nakazono et al, 2001); os cloroplastos apresentam menos membranas de tilacóide (Terashima et al, 2006). Em termos funcionais, apresentam maior taxa fotossintética por unidade de área foliar (Senevirathna et al, 2003); maior proporção entre clorofila a/clorofila b (Engel & Poggiani, 1991;Nakazono et al, 2001); maior quantidade de Rubisco e fotossistemas mais complexos (Terashima et al, 2006). Para seringueiras, embora vários estudos enfoquem atributos da folha (Medri,1977;Gomez & Hamzah, 1980;Medri, 1980;Medri & Lleras, 1981, 1983Lemos Filho et al, 1993;Martins & Zieri, 2003;Miguel et al, 2007, dentre outros), nem sempre o foco são as folhas sombreadas, como os de Martins & Zieri (2003) ou as diferenças entre folhas de sol e de sombra, conforme estudos de Senevirathna et al, 2003. Dados de produção divulgados por Gonçalves et al (2006) mostraram diferenças entre a produtividade de clones de seringueira da série IAC, que foram selecionadas pelo Instituto Agronômico de Campinas, com relação ao clone RRIM 600, de origem asiática e que é o tradicionalmente cultivado nesta região.…”
Section: Introductionunclassified